Adsorption of two microcystins onto activated carbon: equilibrium, kinetic, and influential factors. Issue 50 (26th October 2016) - Zhu, Shumin; Yin, Didi; Gao, Naiyun; Zhou, Shiqing; Wang, Zhaochun; Zhang, Zhengde
Abstract: Microcystins (MCs) are very stable toxins in water bodies and can be poorly removed by traditional drinking water treatment processes. Powder-activated carbon (PAC) was employed in the present study for removal of two commonly and widely occurring algal toxins, microcystin-LR (MC-LR), and microcystin-RR (MC-RR), which were obtained from cyanobacterial blooms. Results indicated that wood PAC has better adsorption capacity on MCs compared with shell and coal PAC. The Freundlich adsorption model can better describe the adsorption behavior of MCs onto PAC. And the pseudo-second-order kinetic model can better fit the adsorption process of MCs onto PAC. Moreover, the adsorption of MCs onto wood PAC was affected by temperature, pH, and anions. The adsorption rates increased with the decreasing temperature. And the adsorption capacity of wood PAC for MCs decreased with the increasing pH. Four kinds of anion hindered the adsorption and reduced the removal rate by 14–24%. Therefore, our study provides valuable information to address the water quality issues caused by microcystins, including selection of the most efficient PAC.